MANPOWER MAINTENANCE CONTRIBUTION TO THE PRODUCTION QUALITY (Case Study of North Bandung Cattle Breeder Cooperative) - Supardi, Endang; Imaniyati, Nani; Mulyati, Sri (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2020)
The problem in this research is the tendency of low quality of production results. This symptom of the low quality of production is thought to arise in the form of consumer dissatisfaction with production or internal quality standards have not been met.Considering the importance of the above problems, between the maintenance of employees with the quality of production results have a strong connection, without the existence of good maintenance will not encourage employees to spend all their abilities for the organization in this case is in producing a good quality product. And vice versa if maintenance can run well will have an impact on improving the quality of production results.The research method used in this study is the survey method. Considering that this research intends to identify the dominant external and internal factors that influence labor maintenance and the quality of production, this research is a verification study, while the method used is descriptive analytic, which is a method to find the relationship between two phenomena.The calculation results obtained that between Maintenance of Workers with Quality of Production Results there is a very close relationship.Meanwhile, based on the results of the significance test, it was found that the quality of production results was influenced by labor maintenance and the rest was influenced by other factors not examined by the authors.From the description above, the writer can conclude that maintenance of labor has a significant relationship to the level of quality of production results.